INVESTIGATING CLIMATE SMART AGRICULTURAL PRACTICES IN LIVESTOCK PRODUCTION IN SOKOTO STATE, NIGERIA: AN APPLICATION OF PRINCIPAL COMPONENT ANALYSIS (FUDMA JOURNAL OF SCIENCES, 2023)
This study sought to investigate the factors influencing the use of climate smart agricultural practices in livestock production in Sokoto State, Nigeria. Multi-stage sampling procedure was used to select 60 respondents for the study. Data analysis was carried out using descriptive statistics, Principal Component Analysis (PCA) and Ordinary Least Square (OLS) regression. The descriptive statistical analysis reveals that the average age of the livestock farmers in Sokoto State was 54 years. Regression results shows that the significant determinants of using climate smart agricultural practices in livestock production were education and communication equipment which were both significant at (p
Keywords: Climate-Smart-Agriculture, Livestock, Principal-Componet-Analysis, Sokoto State